2006
DOI: 10.1093/humrep/dei422
|View full text |Cite
|
Sign up to set email alerts
|

Gender-specific association of the factor V Leiden mutation with fertility and fecundity in a historic cohort. The Leiden 85-Plus Study

Abstract: Fecundity is increased in male FVL carriers; in female subjects, no such association was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 21 publications
1
11
0
1
Order By: Relevance
“…Our results provide an explanation for the increased fecundity found in men with FVL as described in a previous study [12]. In this large case–control study among 1176 subjects, the relative risk of conception within 3 months after marriage was 3.5 (95% CI 2.1–5.7) for men with FVL as compared with men without FVL.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Our results provide an explanation for the increased fecundity found in men with FVL as described in a previous study [12]. In this large case–control study among 1176 subjects, the relative risk of conception within 3 months after marriage was 3.5 (95% CI 2.1–5.7) for men with FVL as compared with men without FVL.…”
Section: Discussionsupporting
confidence: 84%
“…It has long been thought that the high population frequency of FVL reflects some sort of evolutionary benefit for carriers [7–11]. Interestingly, male, but not female, FVL carriers display a higher fecundity rate (the time between marriage and first pregnancy) than non‐carriers [12]. We hypothesized that men with FVL have high sperm counts, thereby increasing their chance to establish a pregnancy and spreading their genotype.…”
Section: Introductionmentioning
confidence: 99%
“…1 Flow diagram of study selection was no association between recurrent miscarriage and frequency of homozygous mutations for factor V (G1691A; Leiden), factor V [H1299R (R2)], factor V (Y1702C), factor II prothrombin (G20210A), factor XIII (V34L), b-fibrinogen ()455G > A), plasminogen activator inhibitor-1 (PAI-1) (4G/5G), human platelet antigen 1 (HPA1) (a/b9L33P), methylenetetrahydrofolate reductase (MTHFR) (C677T) or MTHFR (A1298C). A previous small case-control study has demonstrated that FVL could significantly increase the risk of infertility [25], but this association has not been observed in another study [26]. A role of thrombophilia has also been advised in recurrent IVF failure.…”
Section: Discussionmentioning
confidence: 93%
“…In contrast, we found no evidence for the Foxo1a involvement in female fertility and fecundity, which were respectively defined as the ability to have children, and the probability to conceive within a specific period of time. 25 The other FOXO transcription factor, Foxo3a, has been implicated in a variety of biological processes, including metabolism, fertility, stress response and ageing. In this study, we found no associations between Foxo3a haplotypes, human fertility and fecundity.…”
Section: Discussionmentioning
confidence: 99%